Cracks halting cracks: investigating crack-arresting phenomenon in freshwater ice produced in the laboratory, 2020-2024 ... - Murdza, Andrii; Schulson, Erland; Renshaw, Carl (NSF Arctic Data Center, 2024)
Understanding the behavior of rifts in ice shelves is important for predicting their stability and response to environmental changes. This study investigates the interaction and propagation of cracks in freshwater ice plates, with a focus on the role of secondary notches in inhibiting crack propagation. The experiments were conducted at the Ice Research Laboratory of Dartmouth College's Thayer School of Engineering from 2020 to 2024. The study utilized S2 freshwater laboratory-grown ice specimens (i.e., salt-free), which underwent deep sharp notching perpendicular to their long axes to induce cracking upon bending. Additional specimens featured deeper secondary notches positioned at the ends of primary notches to investigate their influence on crack propagation. Experimental tests, conducted under controlled loading conditions, reveal that deeper secondary notches effectively arrest the propagation of cracks emanating from primary notches. The results suggest that rift propagation inhibition occurs when ...